2014
DOI: 10.1111/j.1532-950x.2014.12255.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and Long‐Term Outcomes After Arthroscopic Treatment of Young Large Breed Dogs With Medial Compartment Disease of the Elbow

Abstract: Some evidence of improvement in long-term function was found in dogs with MCPD after arthroscopic treatment. RUI and cartilage erosion at the time of diagnosis were associated with more lameness preoperatively but did not affect the final gait assessment or osteoarthritis score in this small cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…Determining the agreement between the severity of cartilage damage assessed on radiographs, CT, and arthroscopy was beyond the scope of this study. However, we have previously reported a moderate agreement between radiographic evidence of subchondral bone sclerosis and severity of Outerbridge scores in a subset of the population reported here . Others have confirmed the relationship between radiographic or CT signs of elbow osteoarthritis and arthroscopic evidence of cartilage pathology .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Determining the agreement between the severity of cartilage damage assessed on radiographs, CT, and arthroscopy was beyond the scope of this study. However, we have previously reported a moderate agreement between radiographic evidence of subchondral bone sclerosis and severity of Outerbridge scores in a subset of the population reported here . Others have confirmed the relationship between radiographic or CT signs of elbow osteoarthritis and arthroscopic evidence of cartilage pathology .…”
Section: Discussionsupporting
confidence: 71%
“…Arthroscopic RUI was detected in only 6 of 21 (about 29%) joints at the level of the commissure, reducing the indications for dynamic osteotomies compared with quantitative CT assessment. Evaluation of postoperative outcomes was beyond the scope of this study but has been reported on a subset of this population in a separate article …”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether osteoarthritis was the cause of the elbow lameness after the first treatment or whether osteoarthritis was a consequence of the problem that caused a negative outcome. Progression of radiographic osteoarthritis has also been described in joints with a good clinical outcome after arthroscopic treatment . A large longitudinal study, including CT and arthroscopic findings, comparing treated joints with and without favorable outcomes might answer this question.…”
Section: Discussionmentioning
confidence: 99%
“…,30 A large longitudinal study, including CT and arthroscopic findings, comparing treated joints with and without favorable outcomesVeterinary Surgery 45 (2016) 246-253 © Copyright 2016 by The American College of Veterinary Surgeons might answer this question. Radiography is insufficient to diagnose coronoid lesions because of superimposition of joint structures.…”
mentioning
confidence: 99%
“…Elbow dysplasia is an important cause of forelimb lameness in large breed dogs (Fitzpatrick et al, 2009a; Michelsen, 2013; Barthélémy et al, 2014). The elbow cartilage damage (Fitzpatrick et al, 2009;Michelsen, 2013;Barthélémy et al, 2014).…”
Section: A Introductionmentioning
confidence: 99%